Walking with the enemy [videorecording (DVD)] - Armstrong, Jonas; Kingsley, Ben, 1943-; Tointon, Hannah (20th Century Fox Home Entertainment, 2017)
Based on a true story, it is an unforgettable film of love, courage and sacrifice. During the final months of World War II in Hungary, a young man sets out to find his displaced family by using a stolen Nazi uniform to pose as an officer. On a journey filled with suspense and danger, he undertakes extraordinary measures to save his family and thousands of lives from the enemy.